THE APPARATUS AND TERMINOLOGY OF POLITICAL LINGUISTICS IN ENGLISH: A DETAILED ANALYSIS - Z. S. Alimova (Bright Mind Publishing, 2025)
Political linguistics in English has evolved a precise apparatus—semantic clarity, structural conciseness, pragmatic force, and interdisciplinary scope—to analyze how language shapes political realities. This article reviews key terminological features (e.g., “coalition government,” “snap elections,” “Brexit”), then applies them to the Russia–Ukraine crisis, examining euphemisms like “special military operation,” delegitimizing labels such as “Kyiv regime,” and ideological frames like “denazification.” Drawing on discourse-historical CDA (Fairclough 1995; van Dijk 1998) and Ustyuzhanina’s four-sector typology, it illustrates how semantic precision, compound formations, emotional valence, and cross-sector overlaps enable actors to legitimize authority, manipulate perceptions, and mobilize audiences.
Keywords: Political linguistics, semantic clarity, structural conciseness, pragmatic influence, interdisciplinary discourse, Russia–Ukraine crisis, euphemism, polarization, nominalization, functional dominants.